Buccopharyngeal morphology of the tadpoles of Scinax v-signatus, with comments on larval characters of the S. perpusillus species group (Amphibia: Anura: Hylidae) - Dias, Pedro Henrique Dos Santos; Pie, Marcio R. (Zootaxa, 2021)
The Neotropical genus Scinax Wagler currently comprises 127 species of small treefrogs distributed from southern Mexico to Argentina and Uruguay, including some islands such as Trinidad and Tobago, and St. Lucia (Frost 2020). Two major clades are recognized within Scinax, the S. catharinae and the S. ruber clades. The former is composed of two species groups, the S. catharinae and the S. perpusillus groups (Faivovich 2002; Faivovich et al. 2005). The S. perpusillus species group currently comprises 13 species: S. alcatraz (Lutz); S. arduous Peixoto; S. atratus (Peixoto); S. belloni Faivovich, Gasparini & Haddad; S. cosenzai Lacerda, Peixoto & Feio; S. faivovichi Brasileiro, Oyamaguchi & Haddad; S. insperatus Silva & Alves-Silva; S. littoreus (Peixoto); S. melloi (Peixoto), S. peixotoi Brasileiro, Haddad, Sawaya & Martins; S. perpusillus (Lutz & Lutz); S. tupinamba Silva & Alves-Silva; and S. v-signatus (Lutz). These species are endemic of the Brazilian Atlantic Forest and are recognized by their intimate association with bromeliads (Fig. 1), in which adults breed and lay their eggs, and tadpoles develop (Peixoto 1987, 1995; Alves-Silva & Silva 2009).